Pengaruh Store Atmosphere terhadap Revisi Intention Melalui Customer Experience pada Konsumen Baso Malang Fortuna - Dinurrahman Falih; Novi Kadarini Rahayu (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research intends to examine how the environment of a store impActs the likelihood of customers returning, specifically focusing on the experiences of patrons at Baso Malang Fortuna. The motivation behind this study stems from varying sales outcomes combined with a low propensity for consumers to come back. A quantitative research design was utilized involving survey techniques. Data was gathered by administering questionnaires to shoppers, employing a non-probability sampling approach. The analysis of the data was performed using Structural Equation Modeling (SEM) to investigate both direct and indirect influences among the studied variables. The findings reveal that the store's atmosphere significantly and positively affects customer experience, that the store's atmosphere has a substantial positive influence on the desire to return, and that customer experience also positively and significantly influences the intention to revisit. In addition, customer experience effectively mediates the relationship between the store atmosphere and the intention to return. These results validate that an optimally maintained store atmosphere fosters enjoyable customer experiences, which in turn boosts consumers' desire to return.